Environmental Impact and Remediation of Heavy Metals - Saleh, Hosam M.; Hassan, Amal I. (IntechOpen, 2022)
Heavy metals are a group of metals and metalloids that includes transition metals, lanthanides, and actinides. When released into water, these elements have toxic effects on water quality and surface sediments, affecting environmental parameters such as pH and temperature. Therefore, metals that are harmful to aquatic and terrestrial ecosystems pose a significant threat to plants, animals, and human health. As such, there is increased interest in mitigating the harmful environmental impacts of heavy metals. This book provides a comprehensive overview of heavy metals, their impacts on water, soil, food crops, and cosmetics, and techniques for their remediation. It is organized into three sections: "Heavy Metals and Their Effects on the Environment," "Evaluation of Heavy Metals and Their Risks to Irrigation Water," and "Remediation of Heavy Metals."